2008
DOI: 10.1021/jo800578b
|View full text |Cite
|
Sign up to set email alerts
|

A Solventless Route to 1-Ethyl-3-methylimidazolium Fluoride Hydrofluoride, [C2mim][F]·xHF

Abstract: The ionic liquid 1-ethyl-3-methylimidazolium fluoride hydrofluoride, [C2mim][F] x xHF, has been synthesized through a new, solventless route that excludes halogen metathesis. The byproducts are salts, alcohols, and carbon dioxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Decomposition of the unstable methyl hydrogen carbonate into methanol and carbon dioxide would then provide the capping group for 1,3-dimethylimidazol-2-ylidene (Scheme 8). [57] This procedure was further extended to 1-ethylimidazole [58] and 1-butylimidazole [59] [Equation (24)]. Prolonged heating at high temperature (70-120°C) in sealed tubes was required to complete the transformation in all cases.…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Decomposition of the unstable methyl hydrogen carbonate into methanol and carbon dioxide would then provide the capping group for 1,3-dimethylimidazol-2-ylidene (Scheme 8). [57] This procedure was further extended to 1-ethylimidazole [58] and 1-butylimidazole [59] [Equation (24)]. Prolonged heating at high temperature (70-120°C) in sealed tubes was required to complete the transformation in all cases.…”
Section: Synthesismentioning
confidence: 99%
“…A solvent-less route to 1-ethyl-3-methylimidazolium fluoride that does not require the intervention of chloride salts has also been devised along the same lines. [58] (35)…”
Section: Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, methylimidazolium-2-carboxylates can be easily synthesized with high yields by the one-pot reaction of dimethyl carbonate (DMC) with imidazole derivatives, making them very attractive and accessible compounds [35]. Therefore, they found applications as ligands in organometallic catalysis [3641], as precursors of halide-free ionic liquids [4245], and as organocatalysts in reactions involving carbon dioxide transfer in the formation of ketoacetates [4647] and carboxylation of epoxides [48]. Some of us have recently reported a green application of BMIM-2-CO 2 , highlighting its efficiency for the conversion of raw glycerol to glycerol carbonate by transesterification [49].…”
Section: Introductionmentioning
confidence: 99%
“…9 Very recently, a different synthetic route for FHILs starting from the corresponding alkyl amine and dimethylcarbonate has been reported. 10 Recent work has investigated the application of FHILs as propellants for ion engines 11,12 and as electrolytes for the electrolytic production of porous silicon. 13,14 The authors have already reported some fundamental studies on the physical and chemical properties, electrochemical stability, [15][16][17][18][19][20] and structural characteristics [21][22][23] of FHILs, especially those composed of alkylated cyclic ammonium cations.…”
mentioning
confidence: 99%